Nationalism and Beyond - Nenad Miscevic (Central European University Press, 2001)
""There is nothing quite like this book in the contemporary literature. It fills a salient vacuum and would make a fine contribution to a number of debates."" - Philip Pettit, Professor of Social and Political Theory, Australian National University, Canberra. ""The book offers high-level philosophical analysis of a topical issue, that of nationalism. The author takes a partisan, cosmopolitan position towards his subject. His main aim is to show that cultural isolationism, hostility towards the n...